The maturation of the P1m component in response to voice from infancy to 3 years of age: A longitudinal study in young children - Yoshimura, Yuko (Brain Behav, 2020)
INTRODUCTION: In the early development of human infants and toddlers, remarkable changes in brain cortical function for auditory processing have been reported. Knowing the maturational trajectory of auditory cortex responses to human voice in typically developing young children is crucial for identifying voice processing abnormalities in children at risk for neurodevelopmental disorders and language impairment. An early prominent positive component in the cerebral auditory response in newborns has been reported in previous electroencephalography and magnetoencephalography (MEG) studies. However, it is not clear whether this prominent component in infants less than 1 year of age corresponds to the auditory P1m component that has been reported in young children over 2 years of age. METHODS: To test the hypothesis that the early prominent positive component in infants aged 0 years is an immature manifestation of P1m that we previously reported in children over 2 years of age, we performed a longitudinal MEG study that focused on this early component and examined the maturational changes over three years starting from age 0. Five infants participated in this 3‐year longitudinal study. RESULTS: This research revealed that the early prominent component in infants aged 3 month corresponded to the auditory P1m component in young children over 2 years old, which we had previously reported to be related to language development and/or autism spectrum disorders. CONCLUSION: Our data revealed the development of the auditory‐evoked field in the left and right hemispheres from 0‐ to 3‐year‐old children. These results contribute to the elucidation of the development of brain functions in infants.